Fukushima wastewater release: unanswered questions and global concerns - Okaiyeto, Samuel Ariyo; Sutar, Parag Prakash; Sutar, Parag Prakash; Mujumdar, Arun S.; Mujumdar, Arun S.; Xiao, Hongwei; Xiao, Hongwei (International Journal of Agricultural and Biological Engineering, 2024)
The decision by Japan to begin discharging the Fukushima wastewater into the ocean on August 24, 2023 was followed by protests from several countries, including China, Russia, Korea, Vietnam, and deep concerns from the international community. This decision is related to the aftermath of the Fukushima Daiichi nuclear disaster that occurred in 2011, which destroyed the cooling system of the nuclear power plant and caused the reactor cores to overheat. Much water was used to cool down the reactors fuel rods; about 1.3 million cubic meters contaminated water with highly radioactive material was generated, which can fill more than 500 Olympic swimming pools[1]. In order to reduce the levels of radioactivity, an Advanced Liquid Processing System (ALPS) was used to remove most radioactive contaminants from water. ALPS works by circulating water through a system of tanks and filters, which removes specific contaminants such as cesium and strontium, using a multi-step process that includes coagulation, flocculation, ion exchange, and absorption[1]. Japan's government and some scientists have argued that the ALPS-treated water is safe for release into the ocean. According to their claims, the discharged water poses minimal risk to human health and the environment. However, concerns about the long-term effects of this discharge remain in scientists ‘minds.Keywords: Fukushima, wastewater, nuclear disaster, discharge, radioactive contaminantsDOI: 10.25165/j.ijabe.20241702.9076Citation: Okaiyeto S A, Sutar P P, Mujumdar A S, Xiao H W. Fukushima wastewater release: unanswered questions and global concerns. Int J Agric & Biol Eng, 2024; 17(2): 289–290.